Türkiye Vadeli İşlemler Borsasının Polonya örneği ile karşılaştırılması - Tekçe, Hakan (My University, 2006)
Diskette İngilizce Özet var. Abstract: The banking system , as the main component of the financial system , constitutes a significant part of economic policies. However , banks operate in a highly fragile environment that is affected from domestic and international factors. In recently , a wide range of countries have experienced financial problems. In order to resolve the fragilities in inherent in a bank’s financial condition , and hence to enable healthy functioning of the sector , authorities may choose to intervene and restructure. The aim of this study is to provide a

of banking restructuring policies and performance evaluations. Traditionally , the firs phase in the restructuring process a crisis-stricken banking system appears to be financial restructuring with a view to prevent further bank-runs and rebuilt confidence in the banking system. The second phase is operational restructuring , while the third arrangements and regulations that are aimed at establishing a strong and vigorous structure of banking system. The restructuring efforts in the Turkish banking system has concentrated on financial , operational and structural restructuring. As a result of systemic bank restructuring operations implemented in banking system since the crisis in Turkey , bank restructuring has been completed. Nevertheless , it appears that further operations needed in the areas of operational and structural restructuring in the future. While systemic risk in the banking system has been reduced , efficiency of the Turkish banking , however , leaves to much to be desired when it comes to financing the real economy.
Keywords: Sermaye Piyasası; Vadeli İşlemler Borsası_Polonya; Vadeli İşlemler Borsası_Türkiye